Polygenic‐wide analysis to assess the impact of genetic risk profiles on brain morphometry in the ALFA study: Early imaging changes in cognitively normal subjects at risk of late onset AD. (7th December 2020) - Vilor‐Tejedor, Natalia; Guigó, Roderic; Operto, Greg; Crous‐Bou, Marta; Cacciaglia, Raffaele; Falcon, Carles; Arenaza‐Urquijo, Eider M; Minguillón, Carolina; Fauria, Karine; Molinuevo, Jose Luis; Gispert, Juan Domingo
Abstract: Background: Neurodegenerative diseases are associated with progressive neuronal vulnerability and loss of function, along with an accelerated brain atrophy, which is partly influenced by multiple genetic factors. Polygenic risk scores (PRSs) are used for both identifying the genetic architecture of complex diseases and predict disease genetic risk (GR), as well as testing its shared genetic architecture. In this study we investigated whether a genetic predisposition to neurodegenerative and related complex diseases were associated with brain morphometry in a sample of cognitively unimpaired individuals of the ALFA cohort. Method: A total of 479 participants with available genotype and neuroimaging data were included. PRSs were calculated from the most recent genome‐wide association meta‐analyses for neurodegenerative diseases (Alzheimer's disease (AD), parkinson disease), related complex diseases (stroke, hypertension, hypercholesterolemia, diabetes, depression, cerebrovascular disease (CV)), and susceptibility to AD‐core biomarkers (p‐tau and amyloid Aβ‐42). Association analyses included measures of brain morphometry as outcomes. PRS were standardized for easy interpretation. Associations were estimated using linear regression models. All models were adjusted for age, sex, education, APOE ‐ϵ4 status, and total intracranial volume. Result: Preliminary results suggested increased PRS average of AD, tau and Aβ42 levels, indicating higher genetic risk for ALFA participants [Figure 1]. In addition, we found strong positive correlation patterns between GR of hypertension with diabetes, GR of cholesterol with hypertension and diabetes, and GR of depression with diabetes, hypertension and cholesterol [Figure 2]. Furthermore, the most remarkable results suggested evidence of association between increased risk of cholesterolemia and reduced volumes of left accumbens area, increased risk of CV and reduced volumes of thalamus proper, as well as increased risk of tau and reduced volumes of right thalamus proper and right cerebellum cortex [see Figure 3 for further results]. Conclusion: We identified strong evidence that genetic liability of related cardiovascular diseases and AD‐core biomarkers influences brain morphology in ALFA. In addition, across all diseases, ALFA participants showed increased genetic risk on AD, and AD‐core biomarkers. In further analyses, we will assess the relationship between neuroanatomical differences in the whole brain and PRSs using voxel‐based morphometry analyses.